THE INFLUENCE OF COMMUNICATION AND WORK ENVIRONMENT ON EMPLOYEE JOB SATISFACTION IN PD SEMANGAT JAYA - Dayu Setiawan; Hendri Dunan (ZILLZELL MEDIA PRIMA, 2024)
The purpose of this study is to determine the influence of communication and work environment on employee satisfaction on their performance in PD Semangat Jaya. The research methodology used in this study is a quantitative approach. This study used primary data sources that the author obtained directly from the original source. The data collection approach used included distributing questionnaires to related research participants. This study used Multiple Linear Regression Test with SPSS Version 25 for data analysis. The study findings showed that there was no statistically significant positive relationship between communication (X1) and employee job satisfaction (Y) (sig = 0.092 > 0.05). In addition, the data shows that the work environment (X2) has a good and large influence on job satisfaction (Y) of workers in PD Semangat Jaya, with a significance score of 0.000 < 0.05.